Dispersion of soybean flour in dicyclopentadiene resin for thermoset composite using the ultrasonic‐assisted method. Issue 10 (1st July 2022) - Ma, Fei; Zhang, Yuehong; Thakur, Vijay Kumar; Liu, Leipeng
Abstract: Thermosetting composites based on dicyclopentadiene (DCPD) in the presence of Grubbs' catalyst and soybean flour were prepared by ring‐opening metathesis polymerization. Soybean flour/DCPD suspensions were sonicated to enhance the dispersion degree before adding catalyst. The curing extent, thermal‐mechanical properties, morphology and thermal stability of the cured soybean flour/DCPD composites were systematically investigated using Soxhlet extraction, DSC, DMA, TMA, tensile test, SEM, and TGA. The results showed that the tensile strength of the soybean flour/DCPD composites increased from 60.7 MPa to 75.8 MPa with the increase of soybean flour loading from 0% to 25%, and the T g obtained from DMA also showed an increasing trend from 129.4°C to 155.1°C. Overall, the introduction of soybean flour into DCPD resin improved the thermal‐mechanical properties of the composite and offered decreased cost and enhanced bio‐based content. Abstract : Soybean flour was introduced into DCPD resin to obtain soybean flour/DCPD composite with improved thermal‐mechanical properties, bio‐based content and decreased cost.